2020
DOI: 10.1186/s12891-020-03248-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal location of subtrochanteric osteotomy in total hip arthroplasty for crowe type IV developmental dysplasia of hip

Abstract: Background: When reconstructing a hip with developmental dysplasia and high dislocation, sub-trochanteric shortening osteotomy is typically needed for placing the acetabular component in the appropriate anatomical position. However, the procedure can result in complications such as non-union of the osteotomy. We evaluated the contact area and the coincidence rate between the proximal and distal fragments at different femoral osteotomy levels and lengths. We then determined the optimal location of subtrochanter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…On the other hand, Huang et al. determined the optimal osteotomy position by evaluating the contact area and coincidence rate between the proximal and distal fragments [ 13 ] and demonstrated that a level 1 cm below the lesser trochanter was optimal. Their conclusions support the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Huang et al. determined the optimal osteotomy position by evaluating the contact area and coincidence rate between the proximal and distal fragments [ 13 ] and demonstrated that a level 1 cm below the lesser trochanter was optimal. Their conclusions support the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility of rotational deviation of the stem in the early postoperative period presents a challenge for surgeons. Although one report determined the optimal osteotomy position by evaluating the contact area and coincidence rate between the proximal and distal fragments [ 13 ], no previous study has demonstrated the mechanical effects on the stem and bone. Because femoral osteotomy positioning is an important factor influencing the rotational deviation, the aim of the present study was to use finite element analysis (FEA) to determine the optimal position for osteotomy in THA with an Exeter cemented stem under conditions of full weight-bearing and turning torque.…”
Section: Introductionmentioning
confidence: 99%
“…Nonunion at the osteotomy site may lead to varus angulation, pain, loss of rotational stability, and prosthetic loosening 7,34 . Proper union of the osteotomy site depends on several factors, including the stability of the osteotomy site, 35 size of the contact area between the proximal and distal segments, 22 available bone stock, and degree of vascularization. Among these factors, the stability of the osteotomy site is the most important and is contingent on the osteotomy type, stem fixation method, stem morphology, and use of additional fixation materials such as cables or plate and screws 34,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Bone union at the osteotomy site was assessed using postoperative radiographs based on the criteria for bone union described by Masonis et al [8]. The level of the osteotomy site was measured according to a report published in 2020 [24]. The length of the cemented stem bridging the osteotomy site was also noted.…”
Section: Clinical Data and Radiological Analysismentioning
confidence: 99%
See 1 more Smart Citation